Cutaneous squamous cell carcinoma of the lip successfully treated with rhenium-188 brachytherapy (Dermatology Reports, 2023)
Cutaneous squamous cell carcinoma (SCC) is the second most common form of skin cancer. In most cases, non-invasive SCC has a good prognosis and is curable by surgical resection. Nevertheless, a small percentage of patients pose specific management problems due to the technical difficulty of maintaining function and aesthetics because of the size or location of the tumor. An emerging therapeutic approach with high-dose brachytherapy using a nonsealed rhenium-188 resin, commercially known as Rhenium-Skin Cancer Therapy®, has been shown to be highly effective in non-invasive carcinoma, up to a thickness of 2-3 mm.